Relapsing encephalopathy with cerebellar ataxia related to an ATP1A3 mutation. (23rd September 2015) - Dard, Rodolphe; Mignot, Cyril; Durr, Alexandra; Lesca, Gaetan; Sanlaville, Damien; Roze, Emmanuel; Mochel, Fanny
Abstract : ATP1A3, the gene encoding the α 3‐subunit of the Na + /K + ‐ATPase pump, has been involved in four clinical neurological entities: (1) alternating hemiplegia of childhood (AHC); (2) rapid‐onset dystonia parkinsonism (RDP); (3) CAPOS (cerebellar ataxia, areflexia, pes cavus, optic atrophy, sensorineural hearing loss) syndrome; and (4) early infantile epileptic encephalopathy. Here, we report on a 34‐year‐old female presenting with a new ATP1A3 ‐related entity involving a relapsing encephalopathy characterized by recurrent episodes of cerebellar ataxia and altered consciousness during febrile illnesses. The term RECA is suggested – relapsing encephalopathy with cerebellar ataxia. The phenotype of this patient, resembling mitochondrial oxidative phosphorylation defects, emphasizes the possible role of brain energy deficiency in patients with ATP1A3 mutations. Rather than multiple overlapping syndromes, ATP1A3 ‐related disorders might be seen as a phenotypic continuum.